Simulation of the tensile loading of a cylindrical gel - Mohammad Yasin Abdul Majeed. (2013)
This project serves to highlight the goal of obtaining the theoretical deformation response of a cylindrical soft gel derived when subjected to a tensile load. This is achieved with the aid of higher-order non-elastic models for simulations. The use of the computational software, Mathematica and Matlab will assist in creating simulations of the gel in order to study the complex material behaviour through characterizing elastic constants: λ, μ, l, m and n. λ and μ are called the 2nd order elastic constants while l, m and n are termed 3rd order elastic constants.